Exploring competitive advantage by utilizing Cloud Computing Services (CCS) - Ahmad Taufek, Sazlin; Anwar, Norizan; Abdul Rahman, Safawi; Kurniawan, Yohannes (Faculty of Information Management, 2025)
In today's digital economy, competitive advantage is essential for the success and sustainability of organizations. Organizations that use cloud computing services (CCS) can improve operational efficiency, reduce expenses and increase scalability in addition to promoting innovation and resource utilization. The ability to optimize processes and respond to changing market demands allows businesses to maintain profitability and ensure customer satisfaction. CCS is important for Malaysian Digital (MD) status companies, facilitating alignment with the country's digital transformation agenda, enhancing operational capabilities, and establishing these organizations as leaders in the ASEAN digital economy. Challenges including internet dependency, data security risks and significant upfront investment requirements must be addressed through the establishment of robust digital infrastructure, advanced cyber security frameworks and targeted financial support, especially for smaller enterprises. Policymakers should support these measures to guarantee equitable access to CCS and encourage innovation across multiple sectors. CCS provides a strategic approach to increase long-term competitiveness and innovation, emphasizing its important role in adapting to a rapidly digitizing global economy.